Nightscape of urban squares in landscape architectural design: analysis and evaluations on nightscape of Merdeka Square in Kuala Lumpur - Zahari, Zariff; Hj. Baharuddin, Zainul Mukrim (2016)
Nightscape plays an important role in enhancing the quality of environment especially for urban settings such as the city squares. Declining awareness and negative perceptions may lead to a series ground of crimes, fear and lack of sense of place. The aim of the study is to redefine urban nightscape in realizing a sustainable green and energy-efficient urban squares with the best option of lighting types and its impacts on the community. Through observation and survey, it is found that many factors contributed to the quality of the nightscape of urban square such as the types, orientation and colors or intensity of the lightings. The finding also highlights how the nightscape of an open space really impact on the perception and human behavioural. However, a good nightscape serves the purpose of illumination and positively manipulate the comfort, visual aesthetic and safety of users. And at last, a series of strategies are addressed for the future nightscape designs based on the theoretical studies and sites analyses.